TEKNIK KIMIA DITINJAU DARI PERSPEKTIF FILSAFAT SAINS, FILSAFAT KIMIA DAN FILSAFAT ENGINEERING - Ragil S Dewantoro; Siti Masitoh; Mochamad Nursalim (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Chemical engineering emerged in the early 20th century as a separate body of knowledge that could guide the design and operation of plants. More specifically chemical engineering is the body of knowledge about the design of process plants for producing chemicals or other products whose production involves chemical transformations. Chemical engineering has an important relationship with science, even though this relationship is very different from the usual picture. Although chemical engineering dates back more than 100 years. However, there are still many ordinary people, especially high school or vocational school graduates who will continue their education to a higher level, still feel confused about what chemical engineering is. This study was made with the aim of introducing Chemical engineering further by examining Chemical engineering from the perspective of philosophy of science, philosophy of chemistry and philosophy of engineering. From the results of the study it can be concluded that chemical engineering is a complex field of science consisting of many components such as chemistry, physics, mathematics, mechanics, art, social sciences. All of these components synergize and complement each other in the field of chemical engineering so as to produce reliable engineers who will be ready to face any challenges.